GE_GERICHTE P/15305/2023 vom 30. Oktober 2023 - GE Cour de justice (2023)
ÉGALITÉ DES ARMES;CONTRAINTE(DROIT PÉNAL);ESCROQUERIE;FAUX INTELLECTUEL DANS LES TITRES | CPP.3.al2.letc; CP.181; CP.146; CP.251